Evaluating the Impact of Faults on Broadcasting Protocols for MANETs - Oliveira, Talmai B. de; Costa, Victor F.; Greve, Fabíola; Schnitman, Leizer (Anais do Workshop de Testes e Tolerância a Falhas (WTF); 2006: Anais do VII Workshop de Testes e Tolerância a FalhasDO - 10.5753/wtf.2006.23352, 2006)
Broadcasting in MANETs is a fundamental building block for dealing with routing and reaching consensus. In this kind of network, faults are commonplace. In spite of this, existing broadcast protocols are not adequate to deal with failures present in a real world scenario, such as link failures, network partitions, topology change during broadcasts and momentary node failures. Moreover, the ones that are capable of dealing with faults, are not suitable for MANETs. In this paper, we conduct simulations in order to evaluate the impact of faults on MANET broadcasting protocols under various network scenarios and situations. Although previous studies show that these protocols are very mobile resilient and support well congestion and collisions, the study conducted here show that they are not capable of supporting omission faults. In presence of this type of faults, they are unable to provide a high delivery rate of messages.